1979
DOI: 10.1002/ana.410060408
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the corpus callosum: A study of the frequency of associated malformations

Abstract: Review of 11 cases of agenesis of the corpus callosum studied at our institution revealed a high incidence of associated anomalies. None patients had associated malformations of the central nervous system, 6 involving the pyramidal system. Eight cases were associated with malformations in the rest of the body. Review of completely examined cases from the literature yielded 47 examples of associated malformations. These were varied and without consistent pattern, with the possible exception of facial abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…Moreover, studies of fetuses with ACC have also shown that gyral abnormalities are among the most common additional malformations seen in ACC either on fetal MR imaging or autopsy. 4,9 We also observed a delay in sulcation in many fetuses with ACC. This is particularly interesting because the mechanisms underlying cortical folding are not well understood and are likely complex.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, studies of fetuses with ACC have also shown that gyral abnormalities are among the most common additional malformations seen in ACC either on fetal MR imaging or autopsy. 4,9 We also observed a delay in sulcation in many fetuses with ACC. This is particularly interesting because the mechanisms underlying cortical folding are not well understood and are likely complex.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, additional abnormalities occur frequently with ACC and are best detected by fetal MR imaging. [4][5][6][7][8][9][10] Although the prognostic implications of prenatally detected ACC are not fully understood, evidence suggests that the presence of additional brain abnormalities imparts a worse prognosis. [6][7][8][11][12][13][14][15] We chose to review our experience with cases of ACC and compare them with postnatal cohorts with ACC, to identify associated fetal brain abnormalities that may give insight into the etiology and outcome.…”
mentioning
confidence: 99%
“…15 In the present study, five of the seven cases (71%) had one or more concurrent malformations including encephalocele, meningomyelocele, DandyWalker malformation, orofacial digital syndrome, and trisomy 8. Other CNS anomalies that can be associated with AGCC include interhemispheric cysts, midline li· pomas, and gyral, sulcal, and pyramidal tract anomalies.…”
mentioning
confidence: 99%
“…The most frequent are Dandy-Walker malformation and congenital heart anomalies. Abnormal karyotype (trisomy 18 and 8) are observed at a rate of 20% [10]. Prenatal diagnosis should be suspected in situations of atrium widening and CSP not being observed.…”
Section: Teardrop Signmentioning
confidence: 99%